Three Tier Multiple Choice Test Instrument Design For Analysis Of Student Misconceptions In The Subject Of PPkn - Widiyana, Suci; Rusilowati, Ani; Priyanto, Agustinus Sugeng (Universitas Negeri Semarang, 2019)
Weaknesses and strengths of mastery of the material students in the learning process can be identified using diagnostic tests. This study aims to determine the appropriateness of the contents of the test instrument three tier multiple choice (3TMC) for students' misconceptions analysis. The method used is Research and Development (R&D) with a 4D model consisting of define, design, development and desemination. The analysis technique used is the content validity, content reliability, different power and difficulty level. Analysis of the content validity of the 3TMC test instrument uses the Aiken formula, the reliability test of the 3TMC test instrument uses Interclass Correlation Coefficient (ICC), while the difference power test and difficulty level use Anates. Content validation data was obtained from 5 validators consisting of 3 expert lecturers and 2 PPKn teachers. The results of expert validation of the 3TMC test instruments obtained 20 valid 3TMC items with 19 items having a value of v of 1.00, 1 item with a value of v of 0.60 in item 14. The results of inter-rater reliability analysis showed an Alpha value of 0.938 with avalue Single Measures of 0.750 ≥ 0.5, so it can be seen that the rater agreed in providing an assessment with the criteria of High Reliability. Based on the results of the study it was found that the developed 3TMC test products are valid with little revision and are reliable for use, so that the 3TMC test instrument can be used for the analysis of students' misconceptions on PPKn subjects.